Primary esophageal succinate dehydrogenase deficient epithelioid gastrointestinal stromal tumor: A diagnostic pitfall of poorly differentiated carcinoma - Lu Zhao; Tang-chen Yin; Meng-yuan Shao; Meng Sun; IWeng Lao; Cong Tan; Yuan Li; Lin Yu; Xiao-yan Zhou; Jian Wang (Human Pathology Reports)
Succinate dehydrogenase (SDH)-deficient gastrointestinal stromal tumors (GISTs) are located exclusively in the stomach with a predilection for young adults and children. Occurrences of SDH-deficient GISTs in the extra-gastric location are rather rare. Herein, we presented an unusual esophageal case of SDH-deficient GIST with epithelioid morphology, initially mistaken for poorly differentiated carcinoma. The patient was a 26-year-old male who complained of dysphagia with chest pain. Imaging examinations revealed a submucosal solid mass in the middle esophagus. Histological sections of biopsies showed diffusely distributed or singly scattered epithelioid neoplastic cells with eosinophilic cytoplasm. The immunostaining of epithelial and neuroendocrine markers yielded negative results. Further immunostaining of mesenchymal markers revealed that the neoplastic cells were positive for CD117 and DOG1, with absence of SDHB expression. The morphology and immunophenotype of the resected specimen were consistent with those of the biopsies. Next-generation sequencing detected a nonsense mutation of SDHB gene. Given the different clinical management and outcomes, we proposed that GISTs be included in the differential diagnoses of esophageal epithelioid neoplasms, albeit rare. Awareness of the possibility of SDH-deficient GISTs located outside the stomach, close attention to the suggestive features, and application of ancillary tests, including SDHB immunostaining, would help recognize this unique GIST subtype.